Water quality, feeding management and cost-benefit analysis of a fish hatchery in Jessore district of Bangladesh - Islam, Md Monirul; Hassan, Rashidul; Sharif, BM Newaz; Rahaman, Md Mostafizur; Islam, Md Aminur; Amin, Md Ruhul (Asian Journal of Medical and Biological Research, 2016)
The study was conducted at Ma-Fatema Fish Hatchery in Jessore from January to March, 2016. The present study was emphasized on water quality parameters, feeding management and cost- benefit analysis. The water quality parameters temperature (0C), pH, dissolved oxygen (DO) (mg/l) and transparency (cm) were measured by Celsius thermometer, pH meter, DO meter and secchi disk, respectively. The proximate composition of feed ingredients was determined by the Association of Analytical Chemists, 1980. Brood fishes were reared all year round in the brood ponds by supplying formulated feeds. Temperature was 19oC -26°C in brood ponds and 18oC-24oC in hatching jars; pH was 6.937.87 in brood ponds and 6.79-7.54 in the hatching jars; dissolved oxygen was 4.8-6.3 mg/l in brood ponds and 4.8-6.7 mg/l in hatching jars; transparency was 14-18 cm in the brood ponds. The percentage of farm made feed was protein (27.76%), lipid (4.9%), CHO (18.62%), ash (11.31%), fiber (6.4%), moisture (31.01%). The cost benefit ratios were 1.54, 1.32 and 1.23 and net profits were BDT 49911.67, BDT 24816.67and BDT 16366.67 respectively in January, February and March. Management of brood fish by providing quality feed and physico-chemical parameters of water were maintained in according to scientific procedure. Cost-benefit ratio of the hatchery in common carp production was satisfactory. Asian J. Med. Biol. Res. September 2016, 2(3): 414-421